치과의사 및 치과대학생의 B형 간염 바이러스 표식자의 혈청학적 양상에 관한 연구 - 최영애 (연세대학교 보건대학원, 1985)
[한글] 1965년 Blumberg등이 처음으로 Australia항원을 발견하고 이 항원은 B형간염 바이러스와 특별한 관련이 있음을 보고한 이래로 B형간염의 본태 및 전염경로 그리고 검사방법에 관한 연구가 활발히 이루워져 왔다. 이에 저자는 B형간염 바이러스의 유행지역인 우리나라에서 환자의 혈액이나 타액에 노출이 많은 치과의사 및 치과대학생을 대상으로 HBV표식자의 혈청학적 조사를 시도하여 보았다. 1983년 10월부터 11월까지 사이에 S대학교 치과대학 재학생 234명과 수련중인 치과의사 50명의 혈청을 얻어 B형간염 바이러스 표식자중 HBsAg, HBeAg, Anti-HBc, Anti-HBs에 관하여 RPHA법과 RIA법으로 측정하였다. 이때 대상군을 다시 세분하여 임상을 거치지 않은 1.2학년을 GroupⅠ, 동하계 진료등으로 간염 바이러스에 노출된 기회가 있다고 생각되는 3학년을 GroupⅡ, 임상실습으로 직접 환자를 대하여 GroupⅡ보다 간염 바이러스에 노출된 기회가 더많은 4학년을 GroupⅢ 그리고 매일 환자를 대하므로써 간염 바이러스에 노출될 가능성이 가장 많은 치과의사를 GroupⅣ로 나누었다. 그 결과를 요약하면 다음과 같다. 1. HBsAg양성율은 8.5%였다. 이를 다시 세분하면 GroupI에서는 6.9% GroupⅡ에서는 8.5%, GroupⅢ는 5.5%, GroupsⅣ는 16.0%로 임상경험이 가장 많은 군은 임상경험이 없는 군보다 2.3배나 높았다. 2. B형간염 바이러스 표식자의 혈청학적 양상은 HBsAg, Anti-HBs, Anti-HBc 모두에 음성인 경우가 38.7%, HBsAg음성이나 Anti-HBs 및 Anti-HBc가 양성인 경우가 28.2%, HBsAg 및 Anti-HBs음성이고 Anit-HBc만 양성인 경우가 19%였다. 3. 대상 284명중 HBV표식자 조사에 의하여 B형간염 바이러스의 감염경력이 증명된 것이 GroupⅠ은 52.1%, GroupⅡ는 54.2%, GroupⅢ는 65.9%, GroupⅣ는 76.0%로 임상경험이 많을수록 B형간염 바이러스의 감염율이 높음을 알았다. 4. HBsAg양성자중 HBeAg양성자는 GroupⅠ 및 GroupⅡ에 비해 GroupⅢ 및 GroupⅣ에 유의하게 많았으며 이것은 임상노출에 따른 최근의 기왕증 또는 현증 활동성 간염이 상당수 있었음을 의미하는 것으로 여겨졌다. 이상의 소견을 종합해서 볼때 본조사 대상의 HBsAg양성율에 있어서 임상실습이 없는 치대 1. 2학년생은 우리나라의 같은 연령군에 비해 별 차이가 없었으나 임상이 쌓임에 따라 양성율이 증가함을 알 수 있었다. 이점은 다른 B형간염 바이러스 표식자로 검토한 결과 도 동일한 소견이었으며 특히, HBeAg양성율이 임상경험의 증가와 함께 높아짐은 매우 유의한 소견으로 보아진다. Study on the serological profiles of hebatitis B virus markers in dentists and dental college students Young Ae Choi Department of Public Health Graduate School of Health, Science and Management. (Directed by professor Samuel Y. Lee, M.D.) The prevalence rate of hepatitis B virus (HBV) infection is known to be high in our country. The dentists, who are frequently exposed to patient's blood and saliva, have been considered as one of the high risk groups. As a mean to determine the prevalence rate of HBV infection 50 resident dentists and 234 dental college students were analysed for HBsAg, HBeAg, Anti-HBc and Anti-HBs using RPHA and RIA method. The results were as follows. 1. Twenty four out of 284 subjects were positive (8.5%) for HBsAg. The positive rate of freshman and sophomore (Group Ⅰ) was 6.9%; junior (Group Ⅱ) 8.5%; senior (Group Ⅲ) 5.5% and resident (Group Ⅳ) 16.0% respectively. The positive rate of Group Ⅰ was not different from that of the age matched control group. 2. As to the pattern of HBV markers of 284 subjects, 38.7% were HBsAg(-) Anti-HBs(-) Anti-HBc(-), 28.2% HBsAg(-) Anti-HBs(+) Anti-HBc(+), and 19% HBsAg(-) Anti-HBs(-) Anti-HBc(+) respectively. 3. One hundred seventy four Subjects out of 284 (61.3%) had been infected to HBV proved by the HBV marker studies. This prevalance rate was increased as the dental practice continued, i.e. GroupⅠ was 52.1%, GroupⅡ 54.2%, GroupⅢ 65.9% and GroupⅣ 76.0% respectively. 4. The positive rate of HBeAg was significantly higher in GroupⅢ and Ⅳ than in GroupⅠ and Ⅱ, which could mean that there were considerable number of subjects in the latter groups who had an anamnestic or active HBV infection. [영문] The prevalence rate of hepatitis B virus (HBV) infection is known to be high in our country. The dentists, who are frequently exposed to patient's blood and saliva, have been considered as one of the high risk groups. As a mean to determine the prevalence rate of HBV infection 50 resident dentists and 234 dental college students were analysed for HBsAg, HBeAg, Anti-HBc and Anti-HBs using RPHA and RIA method. The results were as follows. 1. Twenty four out of 284 subjects were positive (8.5%) for HBsAg. The positive rate of freshman and sophomore (Group Ⅰ) was 6.9%; junior (Group Ⅱ) 8.5%; senior (Group Ⅲ) 5.5% and resident (Group Ⅳ) 16.0% respectively. The positive rate of Group Ⅰ was not different from that of the age matched control group. 2. As to the pattern of HBV markers of 284 subjects, 38.7% were HBsAg(-) Anti-HBs(-) Anti-HBc(-), 28.2% HBsAg(-) Anti-HBs(+) Anti-HBc(+), and 19% HBsAg(-) Anti-HBs(-) Anti-HBc(+) respectively. 3. One hundred seventy four Subjects out of 284 (61.3%) had been infected to HBV proved by the HBV marker studies. This prevalance rate was increased as the dental practice continued, i.e. GroupⅠ was 52.1%, GroupⅡ 54.2%, GroupⅢ 65.9% and GroupⅣ 76.0% respectively. 4. The positive rate of HBeAg was significantly higher in GroupⅢ and Ⅳ than in GroupⅠ and Ⅱ, which could mean that there were considerable number of subjects in the latter groups who had an anamnestic or active HBV infection.
보건학과/석사